Detecting negative relations in social networks. (2016) - Kaur, Mankirat; Singh, Sarbjeet
Online social networks are drawing attention to a large number of users who interact with each other to form positive and negative relations. Positive relations are produced from friendship, liking, trust whereas negative relations are outcome of disliking, opposition and distrust. Both relations are treated the same way in many theoretical approaches but due to the difference in their flow characteristics, standard measures such as status and centrality seems to output different results for each tie. This paper presents a survey of analysing ties using network analysis techniques such as influence, power measures and addresses how interpretation of these measures changes when applied on negative ties network. Therefore, measures that have been developed specifically for analysing ties in negative networks and identifying negative nodes in mixed networks are discussed in this work. The effectiveness of measures in identifying negative nodes is compared on the basis of various network parameters.